Gender Identity and Future Thinking About Parenthood: A Qualitative Analysis of Focus Group Data With Transgender and Non-binary People in the United Kingdom - Tasker, Fiona; Gato, Jorge (Frontiers in Psychology, 2020)
The idea that people who identify as transgender or outside the gender binary are not interested in becoming parents has been refuted by several studies. However, both medical unknowns and cis-gendered normativity surround the process of becoming a parent for people identifying as transgender or outside of the gender binary, with little known about the psychosocial impact on the family formation dilemmas of transgender and gender nonconforming adults. Employing Life Course Theory as our theoretical framework, three focus group interviews were conducted with eleven adults who identified as transgender or outside the gender binary. Qualitative data analysis of the focus group interview transcripts was conducted through Thematic Analysis. Three main themes were identified concerning the dilemmas perceived by the nine participants who contemplated future parenthood: (i) Planning to become a parent -- “but am I ready for the big responsibility?”; (ii) who I am doesn’t fit into the cis-gender system of accessing fostering, adoption or fertility services; (iii) my quest for a non-binary or gender appropriate self and the need for flexible future planning centered on reproductive capacity. Overall, thoughts about gender transition were often interwoven with parenthood plans and in a reciprocal fashion the desire and intention to have, or not have, children was implicated in satisfaction with gender transition. The significance of these themes is discussed in relation to how hopes for parenthood could be realized without jeopardizing gender identity and the need for a future focused, flexible, and open-minded approach on the part of fertility and adoption services.